Synthesis and Characterization of Polyphosphonates and Polyurethanes Using Chalcone and DOPO-Chalcone as a Flame Retardant - Cetinkaya, Ilay C.; Yuksel, Gamze; Macit, Caner; Ureyen, Mustafa E.; Eren, Tarik (AMER CHEMICAL SOC, 2021)
We synthesized a series of chalcone-based polyphosphonates and polyurethanes as self-extinguishing flame-retardant polymers and characterized them via FTIR,H- 1, C-13 ,P-31 NMR, HRMS, gel permeation chromatography, and inductively coupled plasma-optical emission spectrometry. The thermal stability of the synthesized polymer series was tested by thermogravimetric and evolved gas analysis under both N-2 and air atmospheres as well as microscale combustion calorimetry analysis. After thermal treatment, residue analysis was carried out using scanning electron microscopy with energy-dispersive X-ray analysis and X-ray photoelectron spectroscopy, and decomposition mechanisms are proposed.
Keywords: chalcone; DOPO; polyphosphonates; polyurethanes; flame retardants; fire mechanism; EPOXY-RESINS; PHOSPHORUS; MECHANISM; PHOSPHAPHENANTHRENE; DERIVATIVES; TOXICITY; MICHAEL; OIL; Materials Science; Polymer Science